Pemodelan SARIMA terhadap Curah Hujan Bulanan di Provinsi Jawa Barat - Mohamad Triwahyu; Muhammad Rheza Firmansyah (Griya Journal of Mathematics Education and Application, 2026)
Rainfall is a hydrometeorological phenomenon that has complex seasonal patterns and temporal fluctuations. This study aims to model monthly rainfall in West Java Province using the Seasonal Autoregressive Integrated Moving Average (SARIMA) approach based on 2015–2024 data. The research stages include data stationarity analysis, model order identification, parameter estimation, and residual diagnostic tests to ensure model validity. The best model selection is carried out by comparing the Root Mean Square Error (RMSE), Mean Absolute Error (MAE), and Mean Absolute Percentage Error (MAPE) values. The analysis results show that the SARIMA model is able to represent seasonal patterns and monthly rainfall dynamics with a good level of accuracy. This model is expected to be a reliable mathematical basis for monthly rainfall forecasting in West Java Province.